Trilingual glossary of demographic terminology : English-Japanese-German, Japanese-English-German, German-Japanese-English = [Sankakokugo taishō jinkōgaku yōgoshū : Ei-Nichi-Doku, Nichi-Ei-Doku, Doku-Nichi-Ei] = Dreisprachiges Glossar der Demographie : Englisch-Japanesch-Deutsch, Japanesch-Englisch-Deutsch, Deutsch-Japanesch-Englisch - Koch, Matthias, 1964-; Harmer, Claus; Coulmas, Florian (Brill, 2007)
A glossary, which acts as a research tool for the study of population. Based on the technical literature in the three languages listed, it comprises more than 7500 technical terms, covering scientific fields such as social demography, population geography, political demography, historical demography, medical demography, biodemography, and others.